Frontispiece: Translating Molecular Recognition into a Pressure Signal to enable Rapid, Sensitive, and Portable Biomedical Analysis. Issue 36 (25th August 2015) - Zhu, Zhi; Guan, Zhichao; Liu, Dan; Jia, Shasha; Li, Jiuxing; Lei, Zhichao; Lin, Shuichao; Ji, Tianhai; Tian, Zhongqun; Yang, Chaoyong James
<x xml:space="preserve">Abstract</x> Biomedical Analysis. Gas pressure can be used as the signal readout for a simple and highly sensitive bioanalytical device as shown by C. Yang and co‐workers in their Communication on page 10448 ff. By combining H2O2 decomposition with an antibody assay, various analytes can be detected.